Expression pattern and clinical significance of MerTK on circulating NK cells in systemic lupus erythematosus - Jianping Guo; Yin Su; Xiao Han; Yin Zhu; Haojie Xu; Ranran Yao; Ziye Wang; Ruyu Liang; Wenwen Pei; Renge Liang (Lupus Science and Medicine, 2025)
Objectives To assess the clinical significance of Mer receptor tyrosine kinase (MerTK) on circulating natural killer (NK) cells in systemic lupus erythematosus (SLE).Methods 63 patients with SLE and 36 healthy controls (HCs) were recruited in this study. Peripheral blood samples were collected from all participants. MerTK expression on circulating NK cells (CD3−CD56+) was detected by flow cytometry. MerTK expression was compared between patients with SLE and HCs or lupus nephritis (LN) and non-LN subgroups, and its correlation with clinical or laboratory features was also investigated. Bioinformatic analysis was conducted to explore the potential function of MERTK in NK cells in SLE.Results MerTK expression on circulating NK cells was significantly higher in patients with SLE than that in HCs. In patients with SLE, NK-cell specific MerTK expression was positively correlated with Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), anti-double-stranded DNA antibody levels, proportions and absolute count of B lymphocytes, but negatively correlated with complement C3, complement C4, proportions and absolute count of NK cells. Moreover, NK-cell specific MerTK expression was significantly higher in the LN group than that in the non-LN group. Bioinformatics analysis revealed that MERTK was one of the dysregulated NK-cell related genes in SLE, and the differentially expressed genes related to MERTK were associated with biological pathways including NK cell activation and response to type I interferon (IFN-I). In vitro study showed that MerTK expression on NK cells was increased after IFN-I treatment.Conclusions The expression of MerTK on circulating NK cells was significantly elevated in patients with SLE, particularly in patients with LN, and was correlated with disease activity and autoantibody titres. MERTK expression may be related to regulation of NK cell activation and induced by IFN-I in SLE. Our findings indicate that circulating NK-cell specific expression of MerTK may play a role in the development and progression of SLE.